Realism as an artistic technique (based on the material of Russian prose of the 2010s) - N.G. Prokhorova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The relevance of this study is determined by the fact that documentary elements have become a sign of modern culture, both elite and mass. The subject under consideration is the genre of epistolary novel, which has intensely developed recently in modern literature. The purpose of the study is to identify the forms of documentary elements, as well as the nature of treatment of the document in the works by contemporary Russian authors. The paper examines the novels characterized by different aesthetic and genre specifics (“The Light and the Dark” by M. Shishkin, “Return to Egypt” by V. Sharov, and “Jacob's Ladder” by L. Ulitskaya), which have become the noticeable phenomena in the Russian literature of the 2010s. The novelty of the research is defined by the literary material and the chosen aspect of study. All the analyzed non-documentary novels are based on the authentic documentary basis, since each of the authors introduces various fictitious documents: letters, diaries, military orders, leaflets, excerpts from newspapers, “family tree”, and synopsis. The paper examines the blurring of the boundaries between the factual and the fictional, the authentic and the absurd, the mythological and the real. It has been proved that the documentary is not necessarily associated with the orientation towards authenticity. The appeal of the writers to documentary forms does not prevent them from textualization of the reality or its mythologization, implementation of the post-modern principle of multiple truths and intellectual richness of the works. The form of letters, diaries, and personal notes is a way of upholding the value of private experience and testifies to the intensification of the sentimental discourse in the literature. The most important conclusion is that the activation of the documentary and the expansion of its boundaries in contemporary culture testifies to the overcoming of postmodernism and transformation of its experience, as well as the advent of a new postmodern era. The obtained results are essential for understanding the changes that occur in the contemporary literary process.